THE INFLUENCE OF WORK FACILITIES, TIME MANAGEMENT, SOCIAL PRESTIGE, AND WORK CULTURE ON WORKPLACE SELECTION BY GENERATION Z IN SOUTH BANDUNG - Gustiawan, Rudi; Hisashi, Rendy Mahardhika; Ismail, Gurawan Dayona; Sofiati (Efi), Nunung Ayu; Sudaryo, Yoyo (International Journal of Cultural and Social Science, 2025)
This study aims to analyze the influence of Work Facilities, Time Management, Social Prestige, and Work Culture on Workplace Selection by Generation Z in the South Bandung area. Generation Z is known to have unique characteristics in choosing a workplace, where aspects of digital convenience, time flexibility, work values, and work environment are top priorities. The approach used is quantitative with the SmartPLS-based Structural Equation Modeling (SEM) method version 4, with a total of 150 respondents selected through purposive sampling techniques. The results of the study show that the variables of Work Facilities, Time Management, and Work Culture have a positive and significant effect on Workplace Selection. Meanwhile, the Social Prestige variable did not show a significant influence. The R-square value of 54.3% indicates that this research model is able to explain more than half of the variability of workplace selection decisions by Generation Z. These findings provide important implications for companies in designing recruitment and retention strategies for young workers, with an emphasis on facility comfort, work flexibility, and adaptive work culture.